Development of a tool to assess suicide potential among Filipino youth. [article]. - Estanislao, Susan A. .
This report details the development of the suicide potential inventory for Filipinos(SPIF). It based on the assumption that self-destructive tendencies are manifested in identifiable and quantifiable thoughts, feelings, and behaviors associated with suicide, The study involves six steps: Content validation, face validation, first trial run, final test administration, item analysis and evaluation of test. Two hundred twenty-two tests items were initially written based on the perceived suicide-related psychological conditions reported by seven clinicians and counseling psychologist,five suicidal individuals, and 16 significant others. This figure was reduced to 150, which were subjected to item inspection, revision, language translation and categorization of items by 11 experts. The preliminary form of the SPIF was then administered to 18 significant others, one suicidal and nine non-suicidal individuals. Items were reviewed and further reduced to 140 for the final test administration to 42 significant others, 58 suicidal, and 50 non-suicidal individuals. Its psychometric properties were eventually established after analysis, leaving 87 items. Results revealed high factor scale inter-correlations between the SPIF sub-scales and total scale scores, with correlation values ranging from .71 to .96. Its internal consistency was determined using Cronbach's Reliability Coefficient Alpha, with values ranging from .87 to .98. A further analysis of the construct validity of the SPIF was established using the contrasted groups method. It significantly differentiated between those suicidal and non-suicidal, with a t-value of 10.75. The final procedure examined the evidence of convergence between the SPIF and the Suicidal Probability scale sub-scales and total scale scores, with coefficients ranging from .51 to .77. The five sub-scales(Hopelessness, negative, self-evaluation, suicide ideation, helplessness, and hostility) were then confirmed to measure suicide potential among Filipino youth.